2021
DOI: 10.3390/polym13183024
|View full text |Cite
|
Sign up to set email alerts
|

Surface Recovery Investigation of Silicone Rubber Composites for Outdoor Electrical Insulation under Accelerated Temperature and Humidity

Abstract: Degradation of silicon rubber due to heat and humidity affect its performance in outdoor applications. To analyze the effects of high temperature and humidity on room temperature vulcanized (RTV) silicone rubber (SiR) and its composites, this study was performed. Five different sample compositions including neat silicone rubber (nSiR), microcomposites (15 wt% silica(SMC 15% SiO2) and 15 wt% ATH(SMC 15% ATH), nanocomposite (2.5 wt% silica(SNC 2.5% SiO2) and hybrid composite (10 wt% micro alumina trihydrate with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Among the polymeric insulators, Room Temperature Vulcanized (RTV) silicone rubber is the best choice for the coating of high-voltage ceramic insulators [ 22 , 23 ]. The dielectric properties of silicone rubber are also influenced due to mechanical stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Among the polymeric insulators, Room Temperature Vulcanized (RTV) silicone rubber is the best choice for the coating of high-voltage ceramic insulators [ 22 , 23 ]. The dielectric properties of silicone rubber are also influenced due to mechanical stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Applying UV stress on silicone rubber in combination with high temperature can further accelerate the LMW diffusion [78]. In a more recent work [79], silicone rubber composites' hydrophobicity recovery improved with accelerated temperature and high humidity. However, it has been shown that accelerated weathering stresses can reduce a significant amount of LMW siloxanes even under dry conditions that could affect the hydrophobicity recovery [80].…”
Section: Effect Of Electrical and Environmental Stresses On Self-heal...mentioning
confidence: 96%
“…The addition of filler shows a marginal reduction in the contact angle. The SR have high contact angle due to the low surface energy of the polar methyl groups in their side chain of SR having surface resistant to water and shows high hydrophobicity [21]. VOLUME XX, 2017…”
Section: A Static Contact Angle and Hydrophobicity Recovery Measureme...mentioning
confidence: 99%
“…The hydrophobicity of silicone rubber recovery is by the diffusion of low molecular weight (LMW) components to the surface. The slow recovery of silicone rubber composites is due to the immobilization of LMW components by the fillers enhancing the recovery time high[21].…”
mentioning
confidence: 99%